Attracting international hotels: Locational factors that matter most. (April 2015) - Assaf, A. George; Josiassen, Alexander; Agbola, Frank W.
Abstract: With the increased international competition facing hotel chains, it is essential that the next destination they enter is the most attractive option possible. The host destinations too have a keen interest in strategically positioning themselves in order to attract international hotels since their presence has several positive effects. Using, for the first time, actual on-location data we investigate the factors that matter most for international hotels when selecting host destinations. Specifically, we identify 23 factors that make a destination an attractive (or unattractive) location for international hotels. We then rank these. The results show that welcomeness, infrastructure, and crime rate are the three most important factors that influence the location of international hotels in host destinations. Highlights: We assess the factors that attract international hotels to tourism destinations. T&T welcomeness and the quality of infrastructure are the most significant factors. The level of corruption and crime rate make a destination less attractive.